KEKERASAN SEKSUAL TERHADAP ANAK DAN KESESATAN HATI NURANI - fransisko sadianto; Yasintus Harjon (Jurnal Anifa: Studi Gender dan Anak, 2023)
The focus of this paper is to examine the deepest motives for acts of sexual violence against children, which have become a new kind of culture in Indonesia. Facts show that solving the problem of sexual violence against children is never finished. The chain of crimes continues and takes many victims, even though various methods have been used. This phenomenon finally motivated the writer to seek and find internal motives beyond the external explanations of existing acts of violence. The methodology used in this paper is a literature review by reading various books, journals, news items, and various information related to the theme being worked on. This study found that besides external motives causing sexual violence against children, there are also internal motives, namely the existence of a deviation of conscience of the perpetrator. Perpetrators of sexual violence against children do not want to listen. Their conscience supports them as a 'witness' and, simultaneously, a 'judge' who makes judgments of good-bad and right-wrong in their decisions or actions. Conscience, as the voice of God, is ignored and not obeyed by the person concerned. On that basis, the author offers an effort that is quite effective in finding a solution for the culture of sexual violence against children, namely the importance of conscience education, which includes cognitive, affective, and cognitive dimensions as well as the customary good. Conscience education is essential so that a person can harmonize his decisions and actions according to God's will as He has implanted it in the inner depths of each person.